Dualism of Criminal Procedural Law in the Handling of Corruption Crimes: A Study on the Relationship between the Corruption Eradication Commission and Conventional Law Enforcement Agencies - Gufroni Gufroni; Annelies Larasati Gufron (Universitas Muhammadiyah Tangerang, 2026)
The dualism of criminal procedural law in the handling of corruption crimes in Indonesia is a consequence of legal policy that categorizes corruption as an extraordinary crime. The establishment of the Corruption Eradication Commission, endowed with special powers of investigation, inquiry, and prosecution, was intended to address the limitations of conventional law enforcement mechanisms under the Indonesian Criminal Procedure Code. However, in practice, the coexistence of these two criminal procedural regimes has generated normative and institutional issues that affect the coherence of the criminal justice system, the distribution of authority among law enforcement agencies, as well as legal certainty and the protection of suspects’ rights. This study aims to analyze the construction of criminal procedural law in corruption cases, the relationship of authority between the Corruption Eradication Commission and conventional law enforcement agencies, and the implications of procedural dualism for the principles of the rule of law. The research employs a normative legal research method, using statutory, conceptual, and literature-based approaches conducted through a systematic review of relevant legal materials. The analysis is grounded in the theories of lex specialis, authority, integrated criminal justice systems, legal certainty, due process of law, and procedural justice. The findings indicate that the dualism of criminal procedural law in corruption cases is not merely normative but also structural and institutional in nature. The absence of clear boundaries of authority and integrated coordination mechanisms between the Corruption Eradication Commission and conventional law enforcement agencies has the potential to fragment the criminal justice system. Furthermore, procedural differences in the handling of corruption cases undermine legal certainty and may weaken the protection of suspects’ rights. Therefore, this study emphasizes the urgency of harmonizing criminal procedural law in corruption cases to ensure that anti-corruption efforts remain effective while remaining consistent with the principles of legal certainty, procedural justice, and the protection of human rights. Keywords: Legal dualism, Corruption crime, Corruption Eradication Commission, Criminal justice system